Complex lesion of the third metacarpophalangeal joint: complete tear of the radial collateral and deep transverse metacarpal ligament - Pedrazzini, Alessio; Dejana, Dario Oliver; Romagnoli, Francesco; Bertoni, Nicola; Pedrabissi, Bianca; Yewo Simo, Henry Claudel; Banchi, Massimo; Vanni, Medina; Pogliacomi, Francesco; Ceccarelli, Francesco; Marenzi, Cinzia; Zanchi, Maria Teresa (Acta Biomedica Atenei Parmensis, 2017)
Injuries of collateral ligaments of MCPs joints are often underdiagnosed but have to be considered serious traumas of the hand. In many cases they concern thumb and rarely long fingers. Closed rupture of the deep transverse metacarpal ligament (DTML) is an unusual parallel injury. Both lesions present similar symptoms included local pain, swelling, ecchymosis and deviation of the finger in flexion and can be misdiagnosed. We describe the treatment of a 34 years old woman who sustained a complex lesion of the soft tissues of third metacarpophalangeal joint with complete close tear of the radial collateral and deep transverse metacarpal ligament following a fall during a walk thus leading to a multiplanar instability. Surgery consisted in mini anchor repair or the collateral ligament tear, direct resorbable suture of DTML and a double k-wire stabilization. Follow up at 11 months has shown excellent functional outcomes.